Effectiveness of Drying Methods to Callisia Fragrans Tea Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Herbal tea is a polyherbal formulation of different medicinal plants that is a rich source of antioxidant. Tea manufacturing processes can greatly affect the oxidation of tea polyphenols. Callisia fragrans is an herbaceous plant with small white fragrant flowers and waxy leaves. Its leaves are used for treatment of different skin diseases, burns and join disorders owing to its biologically active flavonoids, neutral glycol and phospholipids and fatty-acid. In order to better utilization of Callisia fragrans was functional herbal tea, the effect of different drying methods such as sun drying, microwave drying and oven drying to the total phenolic, total flavonoid and antioxidant capacity was investigated. Results revealed that microwave drying was the best option to stabilize the valuable components in this plant during drying.Keywords: Callisia fragrans, Total phenolic, Total flavonoid, Antioxidant, Drying, Herbal.